Por uma visualidade do ballet clássico: entrecruzamentos entre os sentidos das imagens do corpo na historiografia e na prática do ballet clássico - Camargo, Henrique (2018)
The present dissertation is a research project carried out through the Graduate Program in Art and Visual Culture, master's level, of the Faculty of Visual Arts (FAV) of the Federal University of Goiás (UFG), in order to analyze and reflect the visualities and the senses constructed by the images of the classical ballet dancers with the emphasis on the work sur la pointe performed by the female classical dancers. I propose to go through an imagery historiography of classical ballet reflecting on the main female figures, from its emergence in the Renaissance to the romantic period where the use of the pointe shoes was established. To present the complex systematization, bodily elitism and devices involved in the practice of classical ballet in order to construct so-called "perfect" bodies and attain the usefulness necessary to erect "beautiful" images. In this sense I use the theoretical conceptions of the French philosopher Michel Foucault as the genealogy and archeology of power and their perception of the docile bodies followed by several of the dispositive used for the training of the bodies of the classical ballet dancers. Among the various dispositives that make up this training I come to realize a deepening in the artifact pointe shoes that emerged realizing the longed for classic ballet, the weightlessness. The artifact that impresses the classical female ballet dancer with the sense of great pregnance, the lightness, has turned into a dispositive by also requiring correct dressage and training and by disguising pains and injuries to convey such visibility. Expose field research conducted at non-formal classical ballet school with a focal group consisting of practitioners of this art during of choreographic process until the final performance. All steps were illustrated through panels based on the mnemosyne atlas of Warburg and various narratives were constructed to contemplate the discussions inserted here about the possibility of presenting "beautiful" images and emerging senses even with people who do not have a so-called "ideal body".